Interfacing real-time and offline power system simulation tools using UDP or FPGA systems - Scheibe, Christian; Kuri, Ananya; Feng, Yuyao; Zhao, Le; Xiong, Xuejun; La Seta, Piergiovanni; Liang, Xiao Peng; Knödtel, Johannes; Holzinger, Philipp; Reichenbach, Marc; Mehlmann, Gert (Electric Power Systems Research, 2022)
This contribution proposes a coupling interface between the real-time simulation system RTDS Novacor and the Power System Simulation Software PSS/E for electromagnetic transient (EMT) and phasor (RMS) hybrid simulations to enable a performant connection between the domains. For the coupling interface, two implementations with different characteristics in latency and hardware requirements are presented. Firstly, an Ethernet (UDP) based connection and secondly a fiber-based connection using the Aurora protocol. The first approach is purely software based, while the second one requires additional hardware. The technical implementation of the interfaces is explained in detail. The functionality of the interfaces is verified on the basis of an EMT-RMS simulation in a small overhead line test system.
CRIS-Team WoS Importer:2022-10-14